Grasses of Punjab Part I - Sharma, M. (Indian Forester, 1983)
The paper gives an exhaustive ecological account of the grasses of Punjab. Various local uses to which these grasses are put are also discussed. 19 grasses are new to the flora of Punjab Plains. In all 133 taxa comprising of 128 species and 5 additional. Varities has been enumerated along with their general distribution and flowering and fruiting periods. Out of these 19 species are cultivated for various purposes and the rest are wild or naturalized. The paper is a step forward in the compilation of the Flora of reorganised Punjab.